Design, synthesis, and pharmacological evaluation of haloperidol derivatives as novel potent calcium channel blockers with vasodilator activity. - Yicun Chen; Jinhong Zheng; Fuchun Zheng; Jinzhi Wang; Yanmei Zhang; Fenfei Gao; Zhanqin Huang; Ganggang Shi (PLoS ONE)
Several haloperidol derivatives with a piperidine scaffold that was decorated at the nitrogen atom with different alkyl, benzyl, or substituted benzyl moieties were synthesized at our laboratory to establish a library of compounds with vasodilator activity. Compounds were screened for vasodilatory activity on isolated thoracic aorta rings from rats, and their quantitative structure-activity relationships (QSAR) were examined. Based on the result of QSAR, N-4-tert-butyl benzyl haloperidol chloride (16c) was synthesized and showed the most potent vasodilatory activity of all designed compounds. 16c dose-dependently inhibited the contraction caused by the influx of extracellular Ca(2+) in isolated thoracic aorta rings from rats. It concentration-dependently attenuated the calcium channel current and extracellular Ca(2+) influx, without affecting the intracellular Ca(2+) mobilization, in vascular smooth muscle cells from rats. 16c, possessing the N-4-tert-butyl benzyl piperidine structure, as a novel calcium antagonist, may be effective as a calcium channel blocker in cardiovascular disease.